Determinants of China foreign direct investment in Latin America - Ávila-López, Luis Alfredo (2020)
Objective: Analyze the flow of foreign direct investment of the People's Republic of China from 2008 to 2017 in 7 Latin American countries: Argentina, Brazil, Chile, Colombia, Mexico, Peru and Uruguay. Method: The research is quantitative, non-experimental, longitudinal panel, descriptive and explanatory scope. Seven variables were analyzed: gross domestic product, trade balance, inflation, distance from Beijing to the capital of the Latin American country and natural resources, from 2008 to 2017. Results: Research results show that the only variable that currently attracts Chinese investment to Latin America is the size of the economy. Conclusions: The variable that seems to determine the investment in this region it lead based on the size of the economy, which was represented in this analysis with the GDP.